PENILAIAN RGEC PADA PERBANKAN YANG TIDAK MENGALAMI, BERISIKO, DAN MENGALAMI FINANCIAL DISTRESS MENURUT MODEL GROVER - Sari, Fara Anjar; Prasetyia, Ferry (Contemporary Studies in Economic, Finance and Banking, 2024)
LPS has liquidated a total of 117 banks by 2021 due to financial distress and the inability to maintain their health. This study aims to analyze the health level of banks through RGEC concerning banks that do not experience, are at risk of, and experience financial distress. Using a descriptive analysis method, banks are categorized based on three levels of potential financial distress according to Grover or G-Score, then evaluated through RGEC assessments in each bank category. The results indicate that, along with the decrease in G-Score, high NPL and low LDR reflect a greater potential for financial distress. Assessment of GCG through managerial ownership, profitability through ROA is not the sole factor indicating potential financial distress. However, low NIM may reflect a high potential for financial distress. Meanwhile, CAR shows high and very healthy values for all bank categories. This suggests that banks need to improve their health through risk management and increase Grover’s value by enhancing working capital, profits, and assets returns, so that banks can not only increase Grover’s value but also strengthen their position as financial institutions.